Nickel-decorated MoS2/MXene nanosheets composites for electrocatalytic oxidation of methanol. Issue 19 (1st October 2021) - Chandran, Mijun; Raveendran, Asha; Vinoba, Mari; Vijayan, Baiju Kizhakkekilikoodayil; Bhagiyalakshmi, Margandan
Abstract: Nickel incorporated on MoS2 /MXene composites (NiMoS2 /MXene) via a wet impregnation method is used as an anode electrode material for methanol electro-oxidation. X-ray diffraction, X-ray photoelectron spectra, and scanning electron microscopy equipped with energy-dispersive X-ray spectroscopy techniques were used for the confirmation of MoS2 /MXene formation. Textural properties of catalysts were obtained in N2 adsorption-desorption analysis. Electrochemical measurements in 0.1 M KOH demonstrated the better electrocatalytic activity of NiMoS2 /MXene catalysts. The NiMoS2 /MXene system exhibited enhanced electrocatalytic activity for methanol oxidation due to low onset potential offered by Ni, high tolerance toward CO poisoning by MoS2, and high conductivity and high mechanical stability of MXene. NiMoS2 -3/MXene catalysts exhibited high current density, electrochemical active surface area, long-term stability, and low Rct value. Based on the electrochemical results, NiMoS2 /MXene catalysts is a highly electroactive anode material. Hence can be utilized in fuel cell applications such as Direct Methanol Fuel Cell (DMFC). Graphical abstract: Image 1